O Van Gogh ficcional: construções e desconstruções intermidiáticas no cinema - Pedrolo, Fabiana Maceno Domingos (2024)
This research aims at investigating some films that approach about the Dutch painter, Vincent van Gogh, his life and work, more specifically films such as Lust for Life (1956); Vincent and Theo (1990); Van Gogh (1991) and At Eternity's Gate (2018). The analysis of these films aims at understanding the image that has been built about the aforementioned artist over time and how it was built in people’s imagination. In order to interpret this painter’s fictional versions, we understand that the created characters were based on his biography and can present different nuances, points of view and approaches, data that have allowed to obtaining new perspectives from viewers, whether they are familiar with the theme or not. Image, sound, as well as other diegetic elements such as framing, light and editing have helped cinema to go further along time, so, it is possible to concretely visualize the information disseminated about van Gogh throughout history, and with them, analyze how some stereotypes about this artist were established and how they are endorsed or overcome in film productions. Thus, this study aims at realizing van Gogh’s image, a cinematographic character, his fictional constitution, whose form transcends the purely biographical aspects addressed in documentaries, as well as interweaving cinematographic language with pictorial and literary language, to promote an intermedial approach. Based on bibliographic and cinematographic research, we researched about Bazin and Rancière, viewer’s role, as well as authors such as Didi-Huberman and Walter Benjamin to analyze Art as a translation or shadow of reality. In addition to these scholars, others were added during this research to foster a cohesive interarts text to intertwine imagery, textual and pictorial elements that could support one another during films production.